The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s004280050432
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical investigation of catalase and peroxisomal lipid β-oxidation enzymes in human hepatocellular tumors and liver cirrhosis

Abstract: A significant reduction of catalase activity, a peroxisomal marker enzyme, occurs in human hepatic neoplasias, but no information is available on other peroxisomal proteins. We have studied by means of immunohistochemistry four specific proteins of peroxisomes (catalase and three enzymes of lipid beta-oxidation) in human hepatocellular tumors of various differentiation grades from adenoma to anaplastic carcinoma. In all tumors, except the adenomas, the tumor cells contained fewer peroxisomes than extrafocal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
(53 reference statements)
3
30
0
Order By: Relevance
“…The inhibition of catalase can have detrimental effects upon cell survival after oxidative stress. The catalase levels are significantly reduced in tumors of the liver (Litwin et al 1999) and other organs (Lauer et al 1999) as well as in a variety of pathological conditions, such as liver allograft rejection (Steinmetz et al 1998) and after ischemia-reperfusion injury (Singh 1996).…”
Section: Catalasementioning
confidence: 99%
“…The inhibition of catalase can have detrimental effects upon cell survival after oxidative stress. The catalase levels are significantly reduced in tumors of the liver (Litwin et al 1999) and other organs (Lauer et al 1999) as well as in a variety of pathological conditions, such as liver allograft rejection (Steinmetz et al 1998) and after ischemia-reperfusion injury (Singh 1996).…”
Section: Catalasementioning
confidence: 99%
“…It has been demonstrated that human hepatocellular tumor cells contain fewer peroxisomes than extrafocal hepatocytes (48). Neoplastic transformation may affect the biogenesis of this organelle and might thus be responsible for some of the metabolic derangements observed in the disease processes of HCC.…”
Section: Members Of Heat Shock Protein 70 and 90 Familiesmentioning
confidence: 99%
“…The tissue-specific expression of peroxisomal enzymes contributes substantially to the biochemical maturation of cells (15). The presence of peroxisomes has been cytochemically revealed in human breast, colon and liver carcinomas (15)(16) and a relationship is found between the specific activities of some peroxisomal enzymes and the histological tumour grades (15)(16).…”
mentioning
confidence: 99%